Tourist Perception, Compliance and Satisfaction with the Implementation of Diving Codes of Conduct at Three Dive Sites in the Marine Protected Area of Dampier Strait, Raja Ampat - Jesihando Tulung; Ai Romdoni (PROGRAM STUDI PARIWISATA SYARAH, FAKULTAS EKONOMI DAN BISNIS ISLAM, UNIVERSITAS ISLAM NEGERI MATARAM, 2025)
Purpose: This research aims to analyze percepcion, compliance and satisfaction regarding the implementation of the Diving Codes of Conduct at three popular dive sites; Friwen Wall, Lau-Lau and Sauwandarek, located within the Marine Protected Area of Dampier Strait, Raja Ampat. The research highlights the interrelationship among these three variables in supporting conservation-based marine tourism management. Methods: A descriptive qualitative approach supported by simple quantitative data was employed. Thirty tourist divers were purposively selected from the three dive sites. Data were collected using a closed-ended Likert-scale questionnaire developed based on the official Diving Codes of Conduct of Raja Ampat Regency. The analysis was conducted descriptively by calculating the percentage distribution of categories for each research variable. Results: Tourist perceptions of the implementation of the codes of conduct showed consistently high positive values (80–90%). Compliance levels were also high (80–90%), particularly in buoyancy control, maintaining distance from coral structures, and adherence to prohibitions on touching marine organisms. Tourist satisfaction reached 90% across all locations, indicating that the application of the codes of conduct does not diminish recreational quality but instead enhances safety, comfort, and the ecological quality of the diving environment. Contribution: This study provides empirical evidence on the interconnectedness of tourist perceptions, compliance, and satisfaction within tropical marine protected areas. The findings reinforce the literature on responsible diving tourism and offer practical insights for strengthening diver education strategies, standardizing operator briefings, and developing sustainable marine tourism policies in Raja Ampat.